Trauma Audit for Intra-Abdominal Injury in Hospital Pulau Pinang - Hui Gan, Choon; S, Viknesh; Wong, Wai Pheng; Hamid, Sahul (IIUM Medical Journal Malaysia, 2019)
Introduction: Intra-abdominal injury is one of the leading causes of morbidity and mortality in all age groups in the world. Our aim is to review the demography, incidence rates and prevalence of intra-abdominal injury in Hospital Pulau Pinang in a tertiary hospital in Northern region of Malaysia. Materials and Methods: We retrospectively reviewed medical records of patients diagnosed with intra-abdominal injury from January 2016 until December 2017 using an in-house electronic database. Traumatic renal injury was excluded. Diagnosis was confirmed via contrast-enhanced CT scan or exploratory laparotomy. Results: A total of 82 patients were diagnosed with intraabdominal injury over a period of 2 years. There is a male (75.61%) and of Chinese ethnicity (43.90%) predominance. Median age at presentation was 20 years old. The oldest patient was 94 years old and the youngest patient was 9 months old. Commonest etiology was motor vehicle accident (78.04%) followed by traumatic fall (12.19%). The commonest injury was splenic injury (50%) followed by liver injury (39.28%). The majority of patient (59.52%) was treated non-surgically, in which a grade 2 splenic injury patient underwent operation after failing a non-operative management. There were only 2 mortalities among the 34 patients in the operative group. There is a higher incidence among Chinese ethnicity due to skewed distribution of Chinese population in our studied area in relation to total Chinese population in Malaysia. We showed a reduction in negative laparotomy in stable patients with suspected intra-abdominal injury with the utilization of a CT scan. Decision for non-operative management should be tailored to individualized approach accompanied by serial assessment for optimal care. Conclusion: Blunt trauma was the most common type of intra-abdominal injury and the spleen was found to be the most common organ injured.